The Communication Network of Online Prostitution in Twitter - Christiany Juditha (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
Humans widely use Twitter for various communication purposes. One advancement in communication due to the inception of this technology is online prostitution, which enables Twitter users to quickly, openly, and vulgarly flirt. Prostitution is no longer a taboo in Eastern society. This study aims to obtain an overview of online prostitution communication networks on Twitter, using the Social Media Analysis method with Sentimentviz application. The results show that intact communication networks were formed between actors, irrespective of the limited number. Twitter accounts are used to promote commercial sex services by each actor through their timeline and hashtags such as #openbo, #realangel, #bispak, #bisyar. At the group level, some actors have a unique position to help service marketing by retweeting messages and functioning as pimps. As for ego-centered networks, most actors stand-alone without being associated with others in promoting commercial sex services.